Legal Protection For Buyers in Selling and Buying of Land Rights (Case Study of Selong State Court Number 55 / Pdt.G / 2018 / PN.Sel Concerning Unlawful Activities) - Zaenathul Mardiani (International Journal of Multicultural and Multireligious Understanding, 2021)
This study aims to analyze the basis for judges considerations in adjudicating and deciding cases Number 55 / Pdt.G / 2018 / PN.Sel, analyzing legal protection for buyers in buying and selling land rights. The method used is the empirical normative legal research method, using a conceptual approach, statutory approach, and sociology of law approach. The results of this study, first, show the judge's consideration of illegal acts in cases of court decisions based on Article 1365 of the Civil Code. Based on these considerations, the Panel concluded that the documents of evidence submitted by Defendants I and II were not supported by the statements of witnesses, so that Defendants I and II were unable to prove their arguments. as well as the disputed land controlled by Defendant II is an Unlawful Act, however, on the other hand, the plaintiff is able to prove the arguments of the lawsuit through evidence supported by testimony of witnesses, then the plaintiff's claim is declared granted. Second, The form of legal protection that can be provided to buyers is repressive legal protection, this is needed to provide solutions and certainty as well as clarity on the settlement of existing disputes because basically the law protects the buyer because even though it is only made with a receipt and signed by the Village Head then the agreement has met the requirements stipulated in civil law so that the receipt can become a means of evidence, even though it has the power of proof to the extent that it is not yet perfect.